Applications Panel - Bret Taylor, Alex (Prentice Hall, 2007)
You might think GWT is pretty cool technology, but you're probably wondering "who else is using it?" It turns out that application developers have used GWT for a wide variety of apps. Come listen to their experiences at this panel, moderated by Bret Taylor of Google Maps fame.